Veress needle versus direct trocar entry for laparoscopy: a retrospective study - Sinha, Sushma; Malik, Surya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this paper is to compare the outcomes of veress needle entry versus direct trocar for laparoscopy in terms of the duration of the procedure, ease of performance and the complications encountered during each technique. Methods: The present study was conducted on a retrospective basis from April ‘2008 to September 2017, in the dept of Obstetrics and Gynecology, in a 100 bedded hospital, ABGH hospital. All the cases who underwent laparoscopic ligation procedure during this time were taken into account. From 2008 to 2012 traditional technique of veress needle entry was used for access(group -1) but it had been switched over to direct trocar since 2013(group -2) These two groups were compared in terms of the demographic profile, duration of procedure, previous h/o surgical interventions ,ease of performance and various complications encountered during the procedure. Results: The total number of patients who underwent ligation during this period were 1912, which were divided into two groups ,till 2012(veress needle entry group,group-1) 754 patients(39.44%),and after 2012 (direct trocar,group -2) 1158 patients(60.56%).Duration of procedure was 4.5±1.2 min in group 1 which was significantly higher than group 2,2.2±0.8 min(p-value <0.001).Amount of gas required was greater in group 1, 4.9±1.3 lts as compared to group 2,2.4±0.5lts. Conclusions: Direct trocar entry is a reliable alternative to traditional technique for pneumoperitoneum establishment and should be regarded as a part of the surgical armamentarium of a trained laparoscopic surgeon.